Crossing Boundaries - Jonathan Davies; Claire Ogali; Lydia Slobodian; Guyo Roba; Razingrim Ouedraogo (United Nations, 2019)
This report examines how pastoral mobility has been impacted by the creation of unnatural boundaries within landscapes and how societies cope with these constraints through legal or informal arrangements. There are many examples from around the world of efforts to facilitate transboundary movements and transboundary ecosystem management by pastoralists.